Construction of Corruption News with Social Reality on Metro TV and TV One Media - Muh Zaldy; Sumarni Sumai (UIN Fatmawati Sukarno Bengkulu, 2025)
This research aims to analyze how the framing of corruption issues is constructed by Metro TV and TV One in reporting on the Corruption League and how the audience forms social reality on the news through comments on social media. In this study, the method used is qualitative with the Pan and Kosicki framing model analysis and Berger and Luckmann's Social Construction theory. This study focuses on two TV media that are quite popular in society, namely Metro TV and TV One. The results of the analysis show that all elements, Metro TV emphasizes more on the perpetrators of corruption who are made into sarcastic humor, by prioritizing the (Who) aspect so that it can form a critical public opinion towards acts of corruption. Meanwhile, TV One in its entire structure emphasizes the (How) aspect of the role of the government and law enforcement officers, which aims to give the impression that law enforcement is the main step in eradicating corruption. Public comments indicate the process of externalization, objectivation, and internalization of the narratives conveyed by each media. This study emphasizes the importance of understanding media framing and audience participation in shaping social reality in the digital era.